Overcoming Students Pleasure of Online Games at Medan City Private Universities - Daulay, Raihanah; Mahdar, Ahmad Zaky (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
This study aims to find out how to overcome the pleasure of playing online games for college students. The research population is all students at private universities in Medan City who like to play online games and the research sample is 75 people. This study uses a qualitative method. Data collection techniques in this study with the questionnaire used. The results of the study show that playing online games excessively will have a negative impact on students, disrupting their academic activities both on campus and off campus. Frequent online game play by students can cause problems, especially in their social, academic and professional life. More specifically, people who usually attend college spend their time playing online games, which in turn causes their discipline and academic performance to decline. The solution is to offer counseling services that suggest parents can relate to their children more closely, starting to socialize more often. While preventing their children from playing online games, parents are advised to talk to their children, play with them and maintain a pleasant relationship with them. Students who like to play online games receive special attention from the guidance and counseling campus, which includes the functions of supervision (advocacy) and prevention, understanding, and assistance.